This research was conducted to study the effects of pretreatment with white-rot fungi on pulp properties of betung bamboo. Inoculum stocks of white-rot fungi (25 ml) were injected into polybag contained barkless fresh bamboo chips of 1.6 cm in width. Each polybag contained 221.21-230.43 g oven dry weight of chips. Bamboo chips in the polybags were inoculated by P. ostreatus and T. versicolor. Both of them were then incubated for 30 and 45 days in an incubator. Bamboo chips were cooked in open ho - Widya FATRIASARI; Riksfardini Annisa ERMAWAR; Faizatul FALAH; Dede Heri Yuli YANTO; Euis HERMIATI (Departemen Hasil Hutan, IPB, 2009)
This research was conducted to study the effects of pretreatment with white-rot fungi on pulp properties of betung bamboo. Inoculum stocks of white-rot fungi (25 ml) were injected into polybag contained barkless fresh bamboo chips of 1.6 cm in width. Each polybag contained 221.21-230.43 g oven dry weight of chips. Bamboo chips in the polybags were inoculated by P. ostreatus and T. versicolor. Both of them were then incubated for 30 and 45 days in an incubator. Bamboo chips were cooked in open hot soda process. The cooked bamboo chips were then fibrillated using beater hollander and stone refiner. Yield, kappa numbers (TAPPI 236 cm-85) and freeness (CSF) of the pulp were then analyzed. Pulp yield pretreated with P.ostreatus and incubated for 30 days was the highest (increased by control 22.31%), while that pretreated with T.versicolor was the lowest (decreased by control 22.20%). The increasing of incubation time had positive correlation with the reduction of kappa number. Statistic test (ANOVA) at 95% level of confidence show that fungi give significant effect on kappa number, freeness, and kappa number degradation. Besides that fungi, the interaction between fungi and incubation times give significant effect on the yield changes and pulp yield. T. versicolor had better activity in 45 days of incubation. Pulp freeness resulted from this study were still lower than the desired value. Pretreatment of betung bamboo using T. versicolor with 45 days of incubation was considered better than the other treatments. Keywords : Betung bamboo, biopulping, pulp yield, kappa number, degree of freeness